PENGEMBANGAN MODEL PROGRAM TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN KEHUTANAN, PERKEBUNAN DAN PERTAMBANGAN DI KALIMANTAN TIMUR - Pera, Gaspar (Universitas 17 Agustus 1945 Samarinda, 2015)
Model Development Program Social Responsibility and Corporate Environment Forestry, Plantation and mining in East Kalimantan. Social and Environmental Responsibility (TJSL) which can be defined as a Vendor moral responsibility towards their stakeholders, particularly the community around the work area or oprasionality. TJSL can be understood as an attempt commitment to act ethically, operating legally and contribute to economic improvement along with improved quality of life of employees and their families, the local community and the wider community. Related to the disclosure of Social Responsibility and Environment there are some standards to measure the disclosure of social and environmental responsibility, one of which is TJSL disclosure guidelines by the Global Reporting Index of Global Reporting Initiatives (GRI). The guidelines of the GRI is widely used as a benchmark by the researchers to measure the disclosure policy of corporate social responsibility. Through this report, companies demonstrate accountability and transparency in the implementation of social and environmental responsibility. Therefore it is necessary to see (1). Is the company in East Kalimantan has implemented a Social and Environmental Responsibility (TJSL) in accordance with the GRI standards? (2). How to model the development of Social and Environmental Responsibility (TJSL) in accordance with the conditions in East Kalimantan? The purpose of this study are: (1). Identify the activities TJSL, (2). Know and analyze the fit between the disclosure of the implementation of the Social and Environmental Responsibility (GRI standards) and actual conditions (3). Formulating alternatives and developing implementation strategies Social and Environmental Responsibility in accordance with the conditions of East Kalimantan. Research taking samples (purposive sampling) in (1). PT Surya Hutani Jaya (concession / Industrial Plantation Forest) (2). PT Gunta Samba (oil palm) (3). PT Kaltim Prima Coal (coal mining). Explorative study, by combining methods of study documentation (study documentation) from various secondary data sources and methods directly (direct methods), namely in the field of primary data collection by interview (interview) and observation (field observation). In general, the study results showed that the Program of Social and Environmental Responsibility (TJSL) basically implemented by all major land-based company in East Kalimantan, particularly the three companies were to be the case to be investigated, to PT. Hutani Surya Jaya / PT. SHJ (Industrial Plantation Forest); 30.57% of the informants said the company has been run TJSL, 59.06% of the informants said the company does not run TJSL and 10.36% of informants claimed not to know.PT. Gunta Samba / PT. GS (Palm Oil); 27.20% of the informants said the company has been run TJSL, 41.68% of the informants said the company does not run TJSL and 31.17% of informants claimed not to know, And PT. Kaltim Prima Coal / PT. KPC (coal mining); 44.80% of the informants said the company has been run TJSL. 44.20% of informants stated the company does not run TJSL and 11.00% of informants claimed not to know. All three companies are not fully utilizing the criteria Global Reporting Initiative (GRI). Similarly, the General Model Development TJSL program consisting of: Input; Diagnosis and Design; Reference; Rationalization and implementation. It can be proposed three (3) models TJSL development, namely: (1) Model-based TJSL input from Down (Bottom-Up Model); (2) Model-based TJSL input from the Top (Top-Down Model); and Model Two-Way (Bilateral-Matching Model).Thus the government should be of national, provincial first district / city in East Kalimantan is more serious to regulate and control the TJSL program especially for land-based industries. This is because regarding hajad life and future of the people, especially the smaller communities that live in / on and on natural resources exploited by large-scale investors; the Government, in particular the Government of East Kalimantan, it is necessary to consider that TJSL is an integral part of the process National development / Local.